Computer-aided Drug Design and Drug Pharmacokinetic Prediction: A Mini-review - Tabeshpour, Jamshid; Sahebkar, Amirhossein; Zirak, Mohammad R.; Zeinali, Majid; Hashemzaei, Mahmoud; Rakhshani, Sajed; Rakhshani, Saleh (Current Pharmaceutical Design, 2018)
Prediction of pharmacokinetics and drug targeting is a challenge in drug design. There are different types of software that can help to predict the pharmacokinetic profile of a drug. Quantitative structure-activity relationship (QSAR) modeling is used for drug design with less cost. Drug-excipient interactions are predicted by docking tools. Computerized drug target prediction and docking programs offer additional options to predict potential effects and adverse reactions of a given candidate as well as the best orientation of the compound on the receptor active site. Information on the absorption, distribution, metabolism and excretion of the drug in the body can enhance prediction of drug release and distribution in the blood and central nervous system (CNS). Computer- aided drug design and delivery can help to save the time and cost in the process of rational drug development.
Keywords: quantitative structure-activity relationship (QSAR)